DIFFERENCES IN SKILL OF MATERNAL BREASTFEEDING BEFORE AND AFTER GIVING A VIDEO ABOUT DIRECT BREASTFEEDING (DBF) METHOD - Komang Ratih Janaetri; Ni Wayan Armini; Ni Komang Erny Astiti (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2024)
Direct breastfeeding is one of the methods of breastfeeding performed directly when the baby sucks and receives breast milk from the mother's breast. Skill training for breastfeeding mothers can be trained using video media. This study aims to determine the differences in the skill of breastfeeding mothers before and after giving a video on the Direct Breastfeeding (DBF) method. This research is pre-experimental with one group pretest and posttest design. The research was held on the 3rd week of February until the 2nd week of April 2023 with a total of 30 respondents who were taken using purposivesampling technique. The instruments used were video media and skill observation checklist. The intervention was provided for 5 days with a pretest and posttest interval of 4 days. Data analysis using the Wilcoxon test showed the median results before giving a video of 65.90 with a minimum value of 57.90, a maximum of 85.80 and after giving a video the median increased to 83.85 with a minimum value of 80.30, a maximum of 90.40. The results of the Wilcoxon test showed that there was a significant difference with a p-value of 0.001 < 0.05 and all respondents experienced an increase in skills (positive ranks).